Potassium nutrition in sugar cane ratoons cultured in red latosol with a conservationist system - Cavalcante, V. S. [UNESP]; Prado, R. M. [UNESP]; Almeida, H. J. [UNESP]; Silva, T. M.R. [UNESP]; Flores, R. A. [UNESP]; Pancelli, M. A. [UNESP] (Taylor & Francis, 2016)
The aim of this study was to evaluate the effect of potassium addition to the soil in first and second ratoon sugarcane cultures in a conservationist system. The experiment was conducted at the State of Sao Paulo, Brazil, in an Acriferric Red Latosol cultured with a IAC SP 93-3046 cane sugar variety after plant-cane cutting. The experiment involved five potassium treatments and four repetitions in randomized block design. The potassium (K) dosages were 27, 54, 108, and 162 kg K ha−1, and a treatment without potassium. Six months after the start of the experiment, soil samples collected at 0–20 and 20–40 cm in depth were analyzed for K content. Four months after sprouting, plants were evaluated, by tiller numbers, height, diameter, technological analysis of stalks, and nutritional status. In the first ratoon, potassium fertilization increased stalk diameters, increased potassium accumulation in the aerial parts, and increased stalk production. In the second ratoon, there was a water deficiency, and soil application of potassium did not influence plant growth, nutritional status, or production parameters. Application of potassium in cane sugar ratoons did not contribute to stalk technological quality.
Keywords: Plant nutrition; quality; soil fertility; stalk production; straw covering; sugarcane